INVESTIGATION OF THE NOVEL ANDROGEN-DEPENDENT TISSUE FACTOR PATHWAY INHIBITOR REGULATING PROTEIN (ADTRP) AND ITS ROLE IN CORONARY ARTERY DISEASE - Heng, Chew-Kiat (ELSEVIER IRELAND LTD, 2021)
10.1016/j.atherosclerosis.2017.06.643